META-ANALYSIS THE EFFECT OF STEM INTEGRATED PROBLEM BASED LEARNING MODEL ON SCIENCE LEARNING OUTCOMES - Roza, Media; Lufri, Lufri; Asrizal, Asrizal (Jurnal Pendidikan Matematika dan IPA, 2023)
The goal of the research is to analyze the impact of Science,     Technology, Engineering, and Mathematics (STEM) integrated Problem Based Learning methods on science learning. Research methods use meta-analysis. The research method using meta-analysis with the research flow is determining the research topic, developing data selection criteria, conducting library searches, classifying data information, analyzing data, and drawing conclusions. Databases are articles published in Scopus-indexed journals, Sinta accredited, and on Google Scholar. The articles analyzed are those published in the last 5 years, namely from 2017-2021. 22 articles meet the criteria for further analysis. Data analysis techniques use effect size. Effect size values are measured as a whole and grouped based on educational levels, subjects, and types of learning outcomes. The results of the study demonstrated that the use of STEM integrated PBL has a large impact, with an average effect size of 1.036. STEM integrated PBL has a high influence on the college level. Based on the type of subject, the highest effect size average is for biology. Depending on the sort of learning outcome, the highest average size for scientific literacy. It may be stated that the STEM integrated PBL approach is more effective for biology and chemistry, as well as scientific components, in high schools and colleges.